Which measures of cigarette dependence are predictors of smoking cessation during pregnancy? Analysis of data from a randomized controlled trial - Riaz, Muhammad; Lewis, Sarah; Coleman, Tim; Aveyard, Paul; West, Robert; Naughton, Felix; Ussher, Michael (Wiley, 2016)
Aims: To examine the ability of different common measures of cigarette dependence to predict smoking cessation during pregnancy.